المملكة العربية السعودية والقضية الليبية 1945- 1955 - السبعاوي, فهد; السبعاوي, عباس (جامعة الوادي - University of Eloued, 2020)
اهتمت المملكة العربية السعودية بقضايا التحرر والاستقلال لبلدان المغرب العربي، التي كانت واقعة تحت هيمنة الدول الاستعمارية، لا سيما ليبيا التي كانت تحت الاحتلال الايطالي المباشر منذ عام 1911. ويتناول البحث الدعم الذي قدمته المملكة العربية السعودية السياسي للقضية الليبية، في المحافل العربية والدولية، إذ ساهمت المملكة العربية السعودية مع الدول العربية والإسلامية في دعم قضية استقلال ليبيا في جامعة الدول العربية وهيئة الأمم المتحدة منذ عام 1945، والتعريف بها حتى حصول ليبيا على الاستقلال في 24 آذار 1951، ويناقش البحث الدور الذي أدته الحكومة السعودية مع الدول العربية في دعم استقلال ليبيا أثناء مناقشات الجمعية العامة للأمم المتحدة منذ عام 1947 فضلاً عن الجهود التي بذلتها في سبيل العمل على انضمامها الى الأمم المتحدة عام 1955. Abstract: The paper deals with the political and financial support provided by Saudi Arabia for the Libyan Case during Arab and International occasions and the Libyan Case was paid a great interest and support by Saudi Arabia International and Arab occasions, especially its contribution with other Arab countries within the work of the Arab League during 1945 – 1955. On the same hand, Saudi Arabia had a role in supporting the Libyan Case politically, through the diplomatic visits between the two sides which mirrored the depth of relation and its good results towards the National Movement in Libyan. In addition to the diplomatic visits by the officials of the two countries which mirrored the range of seriousness in supporting the Libyan Fighting against the Italy Colonialism. The Saudi supporting for the Libyan Case was not only through the Arab League and United Nations in addition to financial support.
مقال
Keywords: المملكة العربية السعودية ، ليبيا ، جامعة الدول العربية ، الامم المتحدة ، استقلال ، استعمار; the Kingdom of Saudi Arabia, Libya, the League of Arab States, the United Nations, independence, colonialism.